Local perceptions of famine: study of a village in Orissa - Mishra, Arima (2005)
The sociological approach to famines focuses on the study of the affected community and its social responses to the event. But this one-sided focus neglects the responses of other sections of society who, while remaining relatively unaffected, are in ways instrumental in the creation of famine. Thus, the question of how famine is enacted and rendered persistent in a society is yet to be fully answered. This paper draws on observations of a field study conducted in a village in Orissa's Kalahandi district and looks at institutionalised socio-economic relationships and community transactions in the process of production. Famine, in this theoretical construct, appears as a long-drawn process of socio-economic and biological decline, in contrast to accepted notions of famine as an `event'. - Reproduced.
Keywords: Famine - India - Orissa; Famine